Comprehensive Biometric Study on the Invasive Seaweed, Caulerpa mexicana, in the Aegean Sea - Erhan Mutlu; Yaşar Özvarol; Barış Akçalı; Berivan Elif Aslan; Zeynep Narlı; Zeynep Zabun (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
The present study investigates the occurrence and biometry of the invasive seaweed Caulerpa mexicana in the Gulf of İzmir, Aegean Sea, thereby highlighting its ecological implications in a region increasingly affected by biological invasions. The Mediterranean basin, especially the eastern and Aegean parts, is becoming a hotspot for non-native species, and the region may be a place of interest with the occurrence of the C. mexicana species. This research represents the first detailed assessment of its biometric characteristics in the Levant-Aegean Basin. The study's sampling was conducted from May to August 2024 at 321 stations along the Aegean coast, and C. mexicana was identified at only two specific sites. The species was found in shallow coastal waters at depths of 10 m and 15 m with densities of 630 shoots/m² and 469 shoots/m², respectively. Morphometric analysis revealed frond lengths ranging from 10 to 12.5 centimeters and widths from 7 to 9 millimeters, with a significant correlation between frond length and number of pinnae. Environmental parameters such as temperature, salinity, and dissolved oxygen were measured, providing a context for the species' habitat preferences. The findings underscore the invasive potential of C. mexicana and its capacity to perturb local marine ecosystems, highlighting the necessity for persistent monitoring and management strategies to mitigate its deleterious effects.